Effectiveness of mindfulness-based cognitive therapy in reducing depressive symptoms among institutionalised patient with major depression in Sokoto State, Nigeria - Argungu, Musa Zulkiflu (2021)
Depression is the most common and crippling mental illness, it represent the mental health disorder that has significant repercussions into the lives of its sufferers. The burden and disability resulting from depression is significant, and yet depression is largely left untreated and most patients do not receive proper professional care. The present study aims to evaluate the effectiveness of mindfulness-based cognitive therapy (MBCT) on major depressive disorder (MDD) and explore its impact on depressive symptoms reduction, suicidal ideation, and disability among depressive patients in Nigeria. This study was conducted as an experimental design with pre-test, post-test, and eight weeks follow-up. One hundred and one participants aged 18-69 years who met DSM-5 criteria for major depressive disorder were recruited through random cluster sampling from two health centres in Sokoto State, Nigeria, and randomly assigned to two groups (experimental and control group). The experimental group underwent mindfulness-based cognitive therapy (MBCT) for depression, while the control group received regular treatment, not any form of psychotherapy. Data was collected at the baseline, immediately after the intervention and 2 months after the intervention, serving as follow-up. General linear model (GLM), repeated measure was applied to assess the effectiveness of the intervention. Data was analyzed with intention-to-treat principle. The SPSS version 22 software was used for analysis and both descriptive and inferential statistics were presented. Treatment effects were measured with the t-tests, ANCOVA and MANCOVA analysis. Test of significance were set at p-value <0.05 and 95% Confidence Interval (CI). Respondents in the intervention group (MBCT group) showed statistically significance depression score, suicidal ideation and disability [mean = 32.70 (6.35), posttest 1 mean score = 22.50 (6.19), posttest 2 mean score = 18.25 (4.64), F [(2, 34.203); P < 0.001]. Suicide ideation [mean = 18.60 (4.40), posttest 1 mean score = 13.35 (3.35), posttest 2 mean score = 10.90 (2.20), F[(2, 11.700); P < 0.001]. Disability [mean = 19.10 (4.42), posttest 1 mean score 14.10 (4.25), posttest 2 mean score = 9.3 (2.90), F [(2, 9.393); P < 0.001]. While for the control group, the results showed no statistically significance depression score, suicidal ideation and disability [mean = 29.55 (7.35), posttest 1 mean score = 24.90 (2.97), posttest 2 mean score = 23.60 (3.72), F [(2, 28.224); P < 0.532]. Suicide ideation [mean = 17.95 (4.25), posttest 1 mean score = 19.10 (2.69), posttest 2 mean score = 16.90 (1.83), F[(2, 18.459); P < 0.651]. Disability [mean = 18.00 (4.03), posttest 1 mean score 17.85 (3.66), posttest 2 mean score = 18.25 (4.89), F [(2, 15.909); P < 0.870]. The findings of the present study showed that MBCT is effective in reducing depressive symptoms, suicidal ideation and disability score among depressed patients in Sokoto state, Nigeria. The findings of this study have implications for mental clinics, family therapy centres, and psychiatrists who provide treatment for psychiatric patients. In general, the findings also may have implications on counselling psychology theory and specifically on MBCT. Future studies may be needed to replicate the findings and for generalization.